Evaluation and comparison of type I tympanoplasty efficacy and histopathological changes to the tympanic membrane in dry and wet ear: a prospective study. Issue 10 (October 2015) - Shankar, R; Virk, R S; Gupta, K; Gupta, A K; Bal, A; Bansal, S
Abstract Objective: This study aimed to compare the success rate of type I tympanoplasty in active (wet) and inactive (dry) mucosal chronic otitis media. Methods: A prospective study was performed of 35 patients each with dry ear and wet ear undergoing type I tympanoplasty in the Otolaryngology Department, Postgraduate Institute of Medical Education and Research, India. All patients underwent type I tympanoplasty between January 2010 and June 2011 by the post-auricular approach. Samples of the remnant tympanic membrane were sent for histopathological examination. Results: After a minimum follow up of one year, the success rate was 88.6 per cent for dry ears and 80 per cent for wet ears. Neither the type (p = 0.526) nor the presence (p = 0.324) of discharge influenced the success rate. Histopathological examination of the tympanic membrane margins was performed for 46 patients: of these, 19 showed evidence of vascularity and 27 did not. There was no significant difference in success rate between groups (p = 0.115). Conclusion: The success rate was not influenced by the presence of ear discharge at the time of surgery, and tympanic membrane vascularity did not influence graft uptake.